Ashtead Common, Surrey (England): Roman Tileworks - George Bird, David (Rei Cretariae Romanae Fautorum Acta, 2017)
The modern administrative county of Surrey lies to the south and west of London, although the historic county once extended right up to the bank of the River Thames, opposite the city. It has mostly poor soils but is well suited to growing trees; indeed even today, after many years of urban development pressures, it is the most wooded county in England. Not surprisingly therefore, the county is not particularly well known for major sites of the Roman period, although there have been discoveries of national importance. The aim of this note is to draw attention to the recent discovery of a Roman tile kiln with features that seem to be very unusual survivals, and the opportunity is taken to note some of the more interesting products of the tilery.